The Relationship between Sextortion during COVID-19 and Pre-pandemic Intimate Partner Violence: A Large Study of Victimization among Diverse U.S Men and Women - Eaton, Asia A. (Victims & offenders, 2023)
In a large and diverse sample of U. S. adults, we assessed participants’ experience with pre-COVID in-person intimate partner violence (IPV) victimization and with sextortion victimization during COVID to better understand the relationship between these phenomena. Experiencing sexual IPV pre-COVID increased the likelihood that men and women would experience sextortion during COVID. Men, Black and Native women, LGBTQ individuals, and emerging adults more often experienced sextortion during COVID than other groups. Implications for research on technology-facilitated sexual violence and practice with survivors are explored.